Chronic Administration of a Leupeptin-Derived Calpain Inhibitor Fails to Ameliorate Severe Muscle Pathology in a Canine Model of Duchenne Muscular Dystrophy - Childers, Martin K. (Frontiers Research Foundation, 2012)
Calpains likely play a role in the pathogenesis of Duchenne muscular dystrophy (DMD). Accordingly, calpain inhibition may provide therapeutic benefit to DMD patients. In the present study, we sought to measure benefit from administration of a novel calpain inhibitor, C101, in a canine muscular dystrophy model. Specifically, we tested the hypothesis that treatment with C101 mitigates progressive weakness and severe muscle pathology observed in young dogs with golden retriever muscular dystrophy (GRMD). Young (6-week-old) GRMD dogs were treated daily with either C101 (17 mg/kg twice daily oral dose, n = 9) or placebo (vehicle only, n = 7) for 8 weeks. A battery of functional tests, including tibiotarsal joint angle, muscle/fat composition, and pelvic limb muscle strength were performed at baseline and every 2 weeks during the 8-week study. Results indicate that C101-treated GRMD dogs maintained strength in their cranial pelvic limb muscles (tibiotarsal flexors) while placebo-treated dogs progressively lost strength. However, concomitant improvement was not observed in posterior pelvic limb muscles (tibiotarsal extensors). C101 treatment did not mitigate force drop following repeated eccentric contractions and no improvement was seen in the development of joint contractures, lean muscle mass, or muscle histopathology. Taken together, these data do not support the hypothesis that treatment with C101 mitigates progressive weakness or ameliorates severe muscle pathology observed in young dogs with GRMD.